Application of homotopy perturbation method for numeric–analytic solution of system of hyperchaotic ODEs - Chowdhury, Md. Sazzad Hossien; Razali, Nur Isnida; Mt Aznam, Suazlan (Institute For Engineering Research and Publications (IFERP), 2018)
In this study, a numeric hybrid technique combined with homotopy-perturbation method (HPM) is introduced to simulate a class of four dimensional hyperchaotic nonlinear initial value problems (IVPs). To check the stability and efficiency of the method, first we solve the selected problem by the fourth-order Runge-Kutta method (RK4) and then by both standard and hybrid homotopy-perturbation method. Finally, we compare the obtained results by the three methods. Based on the cases selected and investigated, the hybrid HPM is reliable and efficient than the standard HPM for extended time length. The studies done by this works suggest that the hybrid HPM is a powerful alternative approach for solving nonlinear hyperchaotic IVPs..